Proceedings of the 2019 International Conference on Precision Machining, Non-Traditional Machining and Intelligent Manufacturin 2019
DOI: 10.2991/pntim-19.2019.39
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Life Analysis of Electrical Connector Contacts Part Based on ABAQUS/FE-SAFE

Abstract: The reliability of the fatigue life of the contacts part of the electrical connector is an important aspect of the mechanical equipment reliability. Aiming at the reliability problem of fatigue life of 450 series multi-purpose spring electrical connector contacts part, A fatigue life calculation method based on ABAQUS/FE-SAFE for the contacts part of the electrical connector is proposed. By establishing a threedimensional model of the contacts part of the electrical connector, the finite element software ABAQU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 7 publications
(6 reference statements)
1
9
0
Order By: Relevance
“…This is mainly because the insertion of the pin causes the entrance size increment of the jack reed, further resulting in the occurrences of elastic deformation and bending stress at the root of jack reed. This explanation can be directly supported by the investigation of Wang et al, which found that the largest equivalent stress is also located at the same position of the jack reed during 450 series multi‐purpose spring electrical connector insertion and extraction processes 36 . Moreover, Figure 5(B) presents the variation of σ max with the increment of the pin insertion percentage.…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…This is mainly because the insertion of the pin causes the entrance size increment of the jack reed, further resulting in the occurrences of elastic deformation and bending stress at the root of jack reed. This explanation can be directly supported by the investigation of Wang et al, which found that the largest equivalent stress is also located at the same position of the jack reed during 450 series multi‐purpose spring electrical connector insertion and extraction processes 36 . Moreover, Figure 5(B) presents the variation of σ max with the increment of the pin insertion percentage.…”
Section: Resultssupporting
confidence: 57%
“…where Δγ max denotes the shear strain amplitude, Δε n means the normal strain amplitude, σ' f is the fatigue strength coefficient, σ m is the mean normal stress, N f is the number of cycles, b is the fatigue strength index, c is the ductility index, ε' f is the fatigue extension coefficient, and C 1 and C 2 are material constants. Moreover, the above parameters can be calculated by the following equations 36 :…”
Section: Fatigue Lifementioning
confidence: 99%
See 3 more Smart Citations